Enhanced thermal stability of planar perovskite solar cells through triphenylphosphine interface passivation - Thambidurai, Mariyappan (2022)
While extensive research has driven the rapid efficiency trajectory noted to date for organic-inorganic perovskite solar cells (PSCs), their thermal stability remains one of the key issues hindering their commercialization. Herein, a significant reduction in surface defects (a precursor to perovskite instability) could be attained by introducing triphenylphosphine (TPP), an effective Lewis base passivator, to the vulnerable perovskite/spiro-OMeTAD interface. Not only did TPP passivation enable a high power conversion efficiency (PCE) of 20.22 % to be achieved, these devices also exhibited superior ambient and thermal stability. Unlike the pristine device, which exhibited a sharp descend to 16 % of its initial PCE on storing in relative humidity of 10 %, at 85 °C for more than 720 h, the TPP-passivated devices retained 71 % of its initial PCE. Hence, this study presents a facile yet excellent approach to attain high-performing yet thermally stable PSCs.